FURTHER EVIDENCE ON DEFENCE SPENDING AND ECONOMIC GROWTH IN NATO COUNTRIES - (:unkn) unknown (ACAD ECONOMIC STUDIES, 2014)
The main purpose of this paper is to analyze the causal relationships between defence spending and economic growth using the Toda-Yamamoto approach to Granger causality test in the case of selected NATO countries for the period of 1949-2006. NATO countries spend biggest proportion of defence spending in the world. Granger causality test on defence-growth issue employed by number of scholars but this paper is firstly used Toda-Yamamoto approach to granger causality to analyze relationship between defence spending and growth. The results show that unidirectional causality exists in seven NATO countries while for five countries no causal relationships were found. On the other hand, Turkey differs from other countries in that the relationship is bilateral.
Keywords: Defence spending; Turkish economy; Granger causality; NATO; economic growth; Toda-Yamamoto approach; COINTEGRATION; CAUSALITY; INFERENCE; GREECE